3D Integration for NoC-based SoC Architectures - Sheibanyrad, Abbas; Pétrot, Frédéric; Jantsch, Axel.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2011)
Back Cover Copy SERIES: Integrated Circuits and Systems 3D-Integration for NoC-based SoC Architectures by: (Editors) Abbas Sheibanyrad Frédéric Petrot Axel Janstch This book investigates on the promises, challenges, and solutions for the 3D Integration (vertically stacking) of embedded systems connected via a network on a chip. It covers the entire architectural design approach for 3D-SoCs. 3D-Integration technologies, 3D-Design techniques, and 3D-Architectures have emerged as topics critical for current R&D leading to a broad range of products. This book presents a comprehensive, system-level overview of three-dimensional architectures and micro-architectures. •Presents a comprehensive, system-level overview of three-dimensional architectures and micro-architectures; •Covers the entire architectural design approach for 3D-SoCs; •Includes state-of-the-art treatment of 3D-Integration technologies, 3D-Design techniques, and 3D-Architectures.
Three-Dimensional Integration of Integrated Circuits - an Introduction -- The Promises and Limitation of 3-D Integration -- Testing 3D Stacked ICs Containing Through-Silicon Vias -- Design and Computer Aided Design of 3DIC -- Physical Analysis of NoC Topologies for 3-D Integrated Systems -- Three-Dimensional Networks-on-Chip: Performance Evaluation -- Asynchronous 3D-NoCs -- Design of Application-Specific 3D Networks-on-Chip Architectures -- 3D Network on Chip Topology Synthesis: Designing Custom Topologies for Chip Stacks -- 3-D NoC on Inductive Wireless Interconnect -- Influence of Stacked 3D Memory/Cache architectures on GPUs.
Keywords: Electronic circuits; Software engineering; Circuits and Systems; Software Engineering